Integrationist triadic agendas for city research:cases from recent urban studies - Salama, Ashraf M. (Journal of Architecture and Urbanism, 2019)
With more than 60% of the world population living in urban areas, cities are becoming at the centre of attention in academic institutions and government organizations. However, there appears to be a continuous fragmentation in the types of knowledge developed where issues or concerns are always addressed in isolation and many factors critical to a comprehensive understanding of cities towards creating better urban environments are oversimplified at best or ignored at worst. Therefore, the thrust of this paper is to demonstrate the thought processes involved in instigating frameworks, raising questions, and establishing objectives for responsive city research. It aims to present two triadic agendas that untangle the essential components of city research; the first is the Lefebvrian triadic conception on the production of space and the second is the triadic perspective of lifestyles theories for understanding housing developments, typologies, and choices. Contextually, while the theoretical underpinnings of these agendas are developed based on a body of knowledge generated in the context of the Western world, their conceptualisation is adapted to grasp and examine key unique particularities of selected emerging (and globalised) Arab cities in the Gulf region. Calling for the need for a trans-disciplinary thinking paradigm for city research, the two agendas adopt an integrationist approach that is amenable to understanding the urban realities of these cities.